Analisis Penerapan Pengelolaan Keuangan dan Praktik Akuntansi pada UMKM Coffee Shop Jakarta Selatan - Inaya Ramadhani; Dhea Safitri; Nadya Azzahra; Abdul Rofiq; Novita Widiawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study was conducted to analyze the implementation of financial management and accounting practices at a Coffee Shop in South Jakarta operating within the MSME sector, with a focus on the importance of structured financial management and the application of standardized accounting as a fundamental element in supporting business sustainability. The research employed a qualitative descriptive method through interviews, direct observations, and document review. The findings indicate that the Coffee Shop has applied a cash-based recording system and utilizes a simple point of sales (POS) application to monitor cash flow and sales transactions. However, the recording of fixed assets, depreciation calculations, and the recognition of liabilities have not fully complied with the guidelines of FAS MSMEs, resulting in financial information that remains limited, lacks transparency, and does not provide a comprehensive overview of the business’s financial condition. Therefore, this study highlights the need to improve human resource capabilities in accounting and to implement simple yet credible accounting software to support more accurate, efficient, and accountable financial reporting. With more professional financial management, business owners will be better equipped to make strategic decisions, strengthen stakeholder trust, and enhance the competitiveness and long-term sustainability of the Coffee Shop.